Pesantren-Based School Curriculum Integration Model in Indonesia - Jejen Musfah; Rusydi Zakaria; Ahmad Sofyan; Wahdi Sayuti; Kholis Ridho; Fauzan Fauzan; Muawam Muawam (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
The research aimed to analyze religious and general subjects' integration in six Pesantren-Based Junior High Schools, employing a qualitative approach with a case study method. The data were collected through documentation, interview, and observation and analyzed using the flow analysis model. The analysis took several steps: data collecting, data reduction, data presentation, and conclusion. The results showed that the Pesantren-Based School curriculum integrated several disciplines (within and across learners), such as religious subjects and natural sciences or social sciences. Pesantren-Based Curriculum also belongs to a connected model, which connects several topics, concepts, or skills. Integration of religious and general subjects in Pesantren-Based Junior High School was conducted by internalizing the religious values into the general subjects. It took the form of relating the subjects to particular Quran verses, hadith, or Islamic history about the prophet or his companions; adding the numbers of religious subjects; and studying the Kitab Kuning.